PENGARUH EFEKTIVITAS SPIP TERHADAP KUALITAS LAPORAN REALISASI ANGGARAN PADA WILAYAH KECAMATAN BRUNO - , (Politeknik Sawunggalih Aji, 2022)
This study discusses to study and analyze the Effectiveness of the Government Internal Control System (SPIP) on the Quality of Budget Realization Reports in the Bruno District Area. The population in this study were all sub-districts in bruno village and all villages in 18 villages in bruno sub-district. By using saturated samples obtained 27 people as respondents. The type of data used is primary data. The research methods in this thesis are quantitative analysis, data quality test, classic assumption test, and multiple regression analysis test. The independent variables in this study are the control environment, discussion, control activities, information and communication, and monitoring while the dependent variable is the quality of the budget improvement report in the Bruno sub-district area. The results of this study prove the facts related to environmental monitoring, risk evaluation, control activities, information and communication, and significant monitoring of the quality of the budget realization report in the Bruno sub-district area. Formally, the environment controls, on quality, reports, budgets, sub-districts, Brunei, while, assessments, activities, communications, and monitoring, do not match the quality of the budget reports in the Brunei Districts.